Bothridium pithonis (Blainville, 1824) from Rock Python (Python morulus) of National Zoological Garden of Sri Lanka - Udugama-Randeniya, P.V.; Fernando, T.S.P.; Kulasena Fernando, H.K.A.V.A (World Journal of Zoology, 2012)
On post mortem examination of a dead adult female Rock python (Python molurus) specimen in the National Zoological garden, Sri Lanka, tapeworms were collected. The morphologic and morphometrics data allowed to conclude that the tapeworm was Bothridium pithonis
Keywords: Bothridium pithonis; Cestoda; Python morulus; Sri Lank